The Inheritance Pattern of Geculan Bocah Dance in Tanon Hamlet, Ngrawan Village, Getasan Sub-District, Semarang Regency - Anindya Syafa'at Nur Isnaeni; Wiyoso, Joko (Jurnal Seni Tari, 2024)
The people of Tanon Hamlet have developed folk arts, one of which is the Geculan Bocah Dance. Geculan Bocah dance is a manifestation of a children's game. This dance is developed and maintained through a process of inheritance.  Inheritance pattern is an activity that has the purpose of maintaining and developing an art object from time to time to keep it alive in the development of the times. The purpose of the study is to describe the inheritance pattern and performance form of the Geculan Bocah dance in Tanon Hamlet. The method used in the research is a descriptive qualitative method, using sociology and ethnocoreology approaches. Data collection used observation, interview, and documentation techniques. Data analysis was conducted using data collection techniques, data reduction, data presentation, and conclusion. The data validity test used triangulation techniques. The results show that the inheritance pattern of Geculan Bocah dance in Tanon Hamlet adheres to three inheritance pattern systems namely "vertical transmission", "diagonal transmission" and "horizontal transmission". The presentation form of the Geculan Bocah dance has three presentation sequences, consisting of the beginning, middle, and end. There are two-floor patterns, namely straight lines and curved lines. The accompaniment used is bonang barung, demung, saron, kendang, bende, gong, and jedor with witty vocals. The makeup used is witty character makeup and uses warok ponorogo costumes consisting of headbands, vests, pants, jarik, and lilit belts.